Failure Analysis of Deep Composite Roof Roadway and Support Optimization of Anchor Cable Parameters - Chen Li; Wenlong Zhang; Tianhong Huo; Rui Yu; Xidong Zhao; Ming Luo (Geofluids)
The stability of the roadway surrounding rock is the key factor of underground mining. Roof subsidence occurred during roadway excavation in the Menkeqing Coal Mine. For the sake of safety, it was decided to stop tunneling project and strengthen roadway support, which resulted in a delay of the construction period and economic damage. To maintain the stability of the surrounding rock, we carried out a systematic study through field monitoring, theoretical analysis, and numerical simulation. The deformation and failure law of the surrounding rock, roof structure characteristics, and mechanical properties of the surrounding rock were obtained by field monitoring. The failure characteristics and forms of deep composite roof roadway are further analyzed. The key points of stability of the roadway surrounding rock of soft rock composite laminated roof are obtained by theoretical analysis, i.e., improving the effective stress diffusion efficiency of the anchor cable through the reasonable arrangement of the anchor cable. We use FLAC numerical simulation software to study the influence of different supporting parameters of anchor cable on the stress diffusion in the surrounding rock and put forward the optimal parameters. The optimized support parameters have been applied in the field, and the ideal results have been obtained.